Plasmalemma Voltage Noise in Chara corallina - Ferrier, Jack M. (1979)
Voltage noise analysis is applied to plasmalemma ion transport in Chara corallina. There is a component in the noise power spectrum that is probably associated with current fluctuations within passive transport channels, and another component that may be associated either with fluctuations in the number of open channels, or with active transport. The data allow the calculation of time constants that may be attributable to molecular level events in these transport processes.